Constitutive Numerical Model of FRCM Strips Under Traction - Monaco, Alessia; Minafò, Giovanni; D’Anna, Jennifer; Oddo, M. Concetta; La Mendola, Lidia (Frontiers in Built Environment, 2020)
In this paper the tensile behavior of Fiber Reinforced Cementitious Matrix (FRCM) strips is investigated through Finite Element (FE) models. The most adopted numerical modeling approaches for the simulation of the fiber-matrix interface law are described. Among them, the cohesive model is then used for the generation of FE models which are able to simulate the response under traction of FRCM strips tested in laboratory whose results are available in the technical literature. Tests on basalt, PBO and carbon coated FRCM specimens are taken into account also considering different mechanical ratios of the textile reinforcement. The comparison between FE results and experimental data allows validating the adopted numerical modelling approach. Finally, some considerations are provided on the effects of the fiber fabric mechanical ratio and the strength and stiffness of the interface on the tensile capacity of the FRCM strip.